Erectile dysfunction: a window to the heart. (28th April 2015) - Androshchuk, Vitaliy; Pugh, Neil; Wood, Andrew; Ossei-Gerning, Nick
Abstract : Erectile dysfunction (ED) is an early marker of coronary artery disease (CAD) and often manifests before the development of symptomatic CAD. In this case report, we present a 60-year-old man with ED, who demonstrated limited response to the standard management strategies and was subsequently treated with percutaneous pelvic intervention (PPI) of the internal pudendal artery. While on the table for PPI, the patient described a classical history of angina, on which basis he underwent coronary angiography and was found to have narrow proximal left anterior descending stenosis. Coronary artery stent placement was then performed using standard techniques. PPI of pudendal artery stenoses with stents is feasible and can improve cavernosal blood flow and venous leakage as well as erectile function.